Consumer Brand Preference: An Empirical Study of Car Buying in Nepal - Rai, Bharat (Archives of Business Research, 2020)
The main objective of the study is to identify the effect of product attributes, price perception, appearance perception, brand personality and self-congruity on brand preference in the buying of car in Nepalese market. Primary data was used for the study and data were collected through structured questionnaire in the five point Likert scale from car users in Nepalese market. Convenient sampling was used for the study and Kathmandu was the sampling location. 500 questionnaires were distributed to car users among them 394 questionnaires were collected. SPSS software has been used to processing and analyzes the data. Mean, Standard Deviation, Correlation and Regression techniques have been used to analyze the data. The research paper found that there is significant positive relationship between independent variables and dependent variable consumer behavior. Moreover, it is found that, there is significant and positive influence of price perception, appearance perception, brand personality and self-congruity on brand preference and product attributes has no significant influence on brand preference in buying of car in Nepalese market.